PENGARUH METODE BERCERITA KISAH NABI MUHAMMAD TERHADAP PERKEMBANGAN BAHASA ANAK USIA DINI DI KB AL-HADIST - Kurnia, Lita; Aprida, Siti Nurul; Masturiah, Ila (Early Stage, 2024)
Language development is a very important ability to develop from an early age. However, children's language development will not develop if they are not trained and developed. The implementation of the learning method used using the storytelling method without using media, makes students less enthusiastic and feel bored in participating in learning. The type of research used is a descriptive quantitative design. Sampling used probability sampling technique with cluster random sampling technique. The research sample consisted of class (B1) and class (B2) with 21 and 22 students respectively. Data collection techniques using questionnaire observation sheets, interviews and documentation, with research data analysis techniques using test instrument requirements for validity, reality and descriptive statistics. Then the data analysis technique uses a simple regression test, and a hypothesis t test (real level) using SPSS version 23. Based on the research results, the method of telling the story of the Prophet has a significant influence on children's language development in the Curugbitung Al-Hadith KB based on the calculation of the coefficient of determination, The R2 (R Square) value obtained was 0.154, which means that the influence of the variable method of telling the Prophet's stories on children's language development was 15.4% and the remaining 84.6% was influenced or determined by other factors which in this case were not examined by researchers.